2009
DOI: 10.1007/s10096-009-0708-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis of biomarkers in cerebrospinal fluid and serum during invasive meningococcal disease

Abstract: The aim of the present study was to determine the profile of different inflammatory molecules in serum and cerebrospinal fluid (CSF) during invasive meningococcal disease (IMD). Their relationship with IMD severity was also assessed. A cohort of 12 patients with IMD was investigated. Paired serum and CSF samples were obtained at the time of diagnostic and follow-up lumbar puncture and were examined using Luminex® analysis. IMD severity correlated with serum interleukin-6 (IL-6) and interleukin-1 receptor antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
3
6
0
3
Order By: Relevance
“…Second, the cohort of controls included patients that received prophylactic vaccination, which could lead to increased serum levels of inflammatory cytokines and chemokines; significant increases of IL-6, TNF- α , and CRP were shown after flu vaccine [29]. Third, concentrations of IL-1Ra in the sera of enrolled patients were higher than in similar studies; however, the levels were comparable with the data previously published by our group [21]. Finally, the etiological diagnosis of bacterial infection was confirmed only in 43% of patients enrolled in the bacterial infection cohort; however, a similar percentage of etiological diagnosis was observed even in a study with septic patients combining regular cultivation and molecular biology techniques [30].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Second, the cohort of controls included patients that received prophylactic vaccination, which could lead to increased serum levels of inflammatory cytokines and chemokines; significant increases of IL-6, TNF- α , and CRP were shown after flu vaccine [29]. Third, concentrations of IL-1Ra in the sera of enrolled patients were higher than in similar studies; however, the levels were comparable with the data previously published by our group [21]. Finally, the etiological diagnosis of bacterial infection was confirmed only in 43% of patients enrolled in the bacterial infection cohort; however, a similar percentage of etiological diagnosis was observed even in a study with septic patients combining regular cultivation and molecular biology techniques [30].…”
Section: Discussionsupporting
confidence: 71%
“…The most pronounced decrease was demonstrated with serum IL-1Ra levels, a decline that has already been reported for patients with CAP during antibiotic therapy, and similar kinetics were observed with sera from patients having an invasive meningococcal disease, who were treated with third generation cephalosporins [20, 21]. For the followup of antibiotic treatment, serum IL-6 levels seem to be the most often studied cytokine.…”
Section: Discussionsupporting
confidence: 62%
“…Within patients, different cytokine pattern might occur and the analysis of a multliple cytokines might be preferred [19]. With the wider availability of multiparametric tests such as Luminex ® beads, the rapid and synchronous monitoring of numerous cytokines will become feasible and this pattern analysis might unravel patients at risk for favorable or unfavorable outcomes [20]. Studies comparing cytokine levels in patients with HSV encephalitis and non-herpetic acute encephalitis have shown that IL-6 in HSV encephalitis was higher than in non-herpetic acute encephalitis, a condition related to paraneoplastic limbic encephalitis [8,21].…”
Section: Discussionmentioning
confidence: 98%
“…Hohe CSF-IL-6 Konzentrationen bei Patienten mit bakterieller Meningitis waren darüber hinaus mit schlechterem neurologischen Ausgang assoziiert (OR 0,18; 95% CI 0,05-0,69; p = 0,013) [36]. Andererseits war ein rascher Abfall der Liquor-IL-6 Konzentrationen bei Patienten mit invasiver Meningokokkeninfektion mit einem schweren Krankheitsverlauf assoziiert [42].…”
Section: Meningitis/encephalitisunclassified